Petunjuk praktis mengatasi gangguan kesehatan di rumah anda Keith W. Sehnert, Howard Eisenberg ; alih bahasa, Indriani K. Sumadikarya - SEHNERT, Keith W; Sumadikarya, Indriani K; EISENBERG, Howard (1980)
298 hlm ilus 21 cm